ANALISIS PENGEMBANGAN INFRASTRUKTUR MENDUKUNG WISATA AIR ASOL. KAWASAN PULAU HARUKU, MALUKU : PENDEKATAN PERENCANAAN DAN PERANCANGAN DENGAN METODE AHP - Rumihin, Ony Frengky (Departement of Civil Engineering, Universitas Winaya Mukti, 2025)
This study aims to analyze the development of supporting infrastructure for Asol Water Tourism in the Haruku Island area, Maluku, particularly in Negeri Oma, which possesses beautiful natural potential but is constrained by limited tourism facilities and infrastructure. The Analytical Hierarchy Process (AHP) method was used to determine priority development criteria through analysis of pre-construction, construction, and post-construction aspects. The results show that the dominant criterion in the pre-construction aspect is construction engineering with consideration of building structure and the environment, with a priority weight of 0.578. In the construction aspect, the dominant criterion is the application of project control principles related to time, quality, and cost, with a weight of 0.091. Meanwhile, in the post-construction aspect, the dominant criterion is synergy through the involvement of communities, the private sector, and universities to achieve operational independence, with a weight of 0.1156. In conclusion, these three aspects are expected to significantly contribute to the development of high-quality and environmentally conscious tourism facilities and infrastructure for Asol Water Tourism.